The efficacy of alpha-lipoic acid and/or gabapentin on the oxidant-antioxidant system in patients with diabetic polyneuropathy - Komurcu, Hatice Ferhan; Baran, Pervin; Erel, Ozcan; Anlar, Omer (International Journal of Research in Medical Sciences, 2020)
Background: Diabetic peripheral sensorimotor polyneuropathy is the most common complication seen in patients with diabetes mellitus (DM). Oxidant system plays a crucial role in its physiopathology. We investigated the changes in the serum levels of total antioxidant status (TAS), total oxidant status (TOS), paraoxonase-1 (PON1) and oxidative stress index (OSI) to evaluate the antioxidant efficacy of alpha lipoic acid (ALA) and/or gabapentin in patients with diabetic polyneuropathy (DPN). Methods: Sixty-three type 2 DM patients with diabetic polyneuropathy (DPN) were enrolled in the study. Patients with DPN were divided into four groups in terms of their treatment: Group 1 consisted of treatment-naive patients; patients treated with ALA, gabapentin or combination of ALA and gabapentin comprised groups 2, 3, and 4, respectively. The patients received the medications for at least six weeks. Serum levels of TAS, TOS, PON1 and OSI were analyzed. Results: No significant difference was observed between the groups according to the oxidative stress parameters studied. Conclusions: The use of ALA and/or gabapentin in patients with DPN did not significantly affect the oxidative stress parameters, including TAS, TOS, PON1, and OSI.